2011
DOI: 10.1177/0096340211421587
|View full text |Cite
|
Sign up to set email alerts
|

Three Mile Island, Chernobyl, and Fukushima: An analysis of traditional and new media coverage of nuclear accidents and radiation

Abstract: The Internet made an enormous amount of information on Fukushima available, far more than was provided by the media during the Three Mile Island and Chernobyl accidents. While journalists contributed much of the news about Fukushima, citizens actively participated in blogs and on Facebook, Twitter, and YouTube, exchanging views and directing others to important news articles or videos. The Internet also gave the traditional media many opportunities for better coverage, with more space for articles and the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 5 publications
1
82
0
1
Order By: Relevance
“…Friedman [59] showed that the Internet made an enormous amount of information on Fukushima available, far more than was provided by the media during the Three Mile Island and Chernobyl accidents. Moreover, citizens actively participated in blogs and on Facebook, Twitter, and YouTube, exchanging views and directing others to important news articles or videos.…”
Section: Resultsmentioning
confidence: 99%
“…Friedman [59] showed that the Internet made an enormous amount of information on Fukushima available, far more than was provided by the media during the Three Mile Island and Chernobyl accidents. Moreover, citizens actively participated in blogs and on Facebook, Twitter, and YouTube, exchanging views and directing others to important news articles or videos.…”
Section: Resultsmentioning
confidence: 99%
“…The event also prompted the U.S. electric industry to implement additional safety enhancements for existing reactors and other facilities. However, public concern about the safety of nuclear power was roused by this accident, as it was by the nuclear disasters at Three Mile Island and Chernobyl [Friedman, 2011]. One major concern held by those opposing nuclear energy is that a foolproof way to safely dispose of nuclear waste has not yet been discovered.…”
Section: Nuclear Power Public Opinion and Information Environmentmentioning
confidence: 99%
“…Twitter became one of the most popular media platforms in which people shared opinions about the incidents at the Fukushima Daiichi nuclear power plant and deliberated on the perceived risks and implications for nuclear power more generally [Kittle Autry and Kelly, 2012;Binder, 2012;Friedman, 2011;Kinsella, 2012]. However, an analysis of a selected sample of tweets with the keyword "Fukushima Daiichi" or its variants showed that only a small proportion of these tweets contained some mentions of the risks or hazards caused by the accident [Binder, 2012].…”
Section: Nuclear Power Public Opinion and Information Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Son, en definitiva, destinos frecuentes tanto para reunir datos como para difundir información relevante de última hora (Vieweg, 2010). Internet y las redes sociales, por otro lado, dan más oportunidades a los medios tradicionales en la cobertura de catástrofes puesto que ofrecen más espacio para los artículos y la posibilidad de incluir gráficos interactivos y vídeos, entre otros elementos (Friedman, 2011).…”
Section: La Cobertura Periodística De Catástrofes Naturales: Estado Dunclassified